The Cambridge photographic atlas of galaxies - König, Michael 1966- (Cambridge University Press, 2017)
Galaxies - the Milky Way's siblings - offer a surprising variety of forms and colours. Displaying symmetrical spiral arms, glowing red nebulae or diffuse halos, even the image of a galaxy can reveal much about its construction. All galaxies consist of gas, dust and stars, but the effects of gravity, dark matter and the interaction of star formation and stellar explosions all influence their appearances. This volume showcases more than 250 of the most beautiful galaxies within an amateur's reach and uses them to explain current astrophysical research. It features fantastic photographs, unique insights into our knowledge, tips on astrophotography and essential facts and figures based on the latest science. From the Andromeda Galaxy to galaxy clusters and gravitational lenses, the nature of galaxies is revealed through these stunning amateur photographs. This well illustrated reference atlas deserves a place on the bookshelves of astronomical imagers, observers and armchair enthusiasts
Originally published in German as Binnewies/König, Bildatlas der Galaxien, 2016. - Title from publisher's bibliographic system (viewed on 15 Sep 2017)
Keywords: Galaxies -- Atlases; Astronomy -- Charts, diagrams, etc; Stars -- Clusters -- Atlases; Galaxie; Astrofotografie; Atlas; Bildband